COMMON MENTAL DISORDERS AMONG HEALTHCARE STUDENTS - Ferreira Santana, Flávia; de Freitas Gomes Ruas, Edna; Regina Queiroz, Priscila; Steil Siewert, Josiane; D`Paula Ribeiro Vieira Torres, Jaqueline; de Almeida Souza Torres, Silvério; Batista Antunes Junior, Geraldo; Ferreira Moura Ribeiro, Eduardo; de Andrade Costa, Amanda; Coelho Azevedo, Gizelle; Fagundes Souto, Daniella; Cristina Santos Alves, Elaine; et al. (Health and Society, 2026)
The present study aimed to evaluate the factors associated with mental disorders among health area students. An integrative literature review was conducted, analyzing articles retrieved from the secondary databases Virtual Health Library, Latin American and Caribbean Literature in Health Sciences, Scientific Electronic Library Online, and Online System for Search and Analysis of Medical Literature using the descriptors common mental disorders; student; and university. The assessment of factors associated with mental disorders among health science students highlights that academic training in these courses is permeated by a level of stress that exceeds the limits of healthy adaptation; the study showed that the prevalence of symptoms of anxiety, depression, and sleep disorders is intrinsically linked to a combination of institutional and psychosocial factors, with particular emphasis on excessive workload, academic competitiveness, and early exposure to suffering and death. To reverse the identified scenario, it is imperative that higher education institutions go beyond a purely technical focus and implement robust psychopedagogical support policies, support groups, and a review of the curriculum structure.